Seroconversion Rate After SARS-CoV-2 Infection and Two Doses of Either ChAdOx1-nCOV COVISHIELD™ or BBV-152 COVAXIN™ Vaccination in Renal Allograft Recipients: An Experience of Two Public and Private Tertiary Care Center - Prasad, Narayan; Bansal, Shyam Bihari; Yadav, Brijesh; Manhas, Neha; Yadav, Deependra; Gautam, Sonam; Kushwaha, Ravishankar; Singh, Ankita; Bhadauria, Dharmendra; Yachha, Monika; Behera, Manas Ranjan; Kaul, Anupama (Frontiers in Immunology, 2022)
Vaccination is an effective strategy for preventing SARS-CoV-2 infection and associated mortality. Renal Transplant Recipients (RTRs) are vulnerable to acquiring infection and high mortality due to their immunocompromised state. Varying responses to the different vaccines, depending on types of vaccines and population, have been reported. Vaccines supply is also limited. The current study evaluated the seroconversion rate after SARS-CoV-2 infection and 2 doses of either COVAXIN™ or COVISHIELD™ vaccination in RTR. Methods The serum anti-SARS-CoV-2 spike protein neutralizing antibody titer was measured in 370 RTRs who acquired SARS-CoV-2 infection (n=172), yet not vaccinated; and those vaccinated with COVAXIN™ (n=78), and COVISHIELD™ (n=120) by chemiluminescence microparticle immunoassay methods from serum. Result Overall, the seroconversion rate either after vaccination or infection was 85.13% (315/370). The vaccine-associated seroconversion was 80.30% (159/198). SARS-CoV-2 infection-associated seroconversion was 90.69% (156/172), COVISHIELD™ associated seroconversion was 79.2% (95/120), and COVAXIN™ associated seroconversion was 82.05% (64/78). The median IgG titer in the SARS-CoV-2 infection group was 646.50 AU/ml (IQR: 232.52-1717.42), in the COVAXIN™ group was 1449.75 AU/ml (IQR: 400.0-3068.55), and the COVISHIELD™ vaccination group was 1500.51 AU/ml (IQR: 379.47-4938.50). The seroconversion rate and antibody titers were similar irrespective of the place of sampling. Patient’s age-associated seroconversion in <45 years was 88.01% (213/242), 45.1-60 years was 83.18% (94/113), and > 60 years was 58.3% (7/12). Conclusions Both infection and vaccination induce robust antibody formation in RTRs. The seroconversion rate after SARS-CoV-2 infection was higher but with a lower antibody titer than vaccines. The vaccines, COVAXIN™ and COVISHIELD™, induce more elevated antibody titers than natural infection. The seroconversion rate and antibody titer in Indian RTRs appears to be better than in the western population, irrespective of their vaccination status.